2009
DOI: 10.1111/j.1365-2036.2008.03925.x
|View full text |Cite
|
Sign up to set email alerts
|

Mercaptopurine treatment should be considered in azathioprine intolerant patients with inflammatory bowel disease

Abstract: SUMMARY BackgroundAdverse drug reactions are a significant reason for therapeutic failure during thiopurine treatment of inflammatory bowel disease. Some smaller series in this patient population have shown that a switch to mercaptopurine may be successful in many cases of azathioprine intolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
77
1
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(84 citation statements)
references
References 31 publications
2
77
1
4
Order By: Relevance
“…A significant number of IBD patients will experience side effects with azathioprine, leading to discontinuation of therapy in up to 60% of patients [69]. Several studies have shown that some azathioprine-intolerant UC patients benefit from a switch to mercaptopurine [70,71]. In case of intolerance to both azathioprine and mercaptopurine, thioguanine can be considered as an alternative maintenance therapy.…”
Section: Thiopurinesmentioning
confidence: 97%
“…A significant number of IBD patients will experience side effects with azathioprine, leading to discontinuation of therapy in up to 60% of patients [69]. Several studies have shown that some azathioprine-intolerant UC patients benefit from a switch to mercaptopurine [70,71]. In case of intolerance to both azathioprine and mercaptopurine, thioguanine can be considered as an alternative maintenance therapy.…”
Section: Thiopurinesmentioning
confidence: 97%
“…Other potential adverse events associated with azathioprine include allergic reactions, rash, fever, headache, fatigue, anorexia, cholestatic hepatitis, and arthralgias. Approximately 50 % of patients who discontinue azathioprine due to adverse events can subsequently tolerate 6-MP, but this should not be prescribed to patients who experienced bone marrow suppression or pancreatitis [ 44 ].…”
Section: Thiopurine Immunosuppressivesmentioning
confidence: 99%
“…Digestive intolerance might be due to the imidazole compound, liberated by the AZA transformation into 6MP raising the possibility that indeed such side effects could be avoided in 1 ⁄ 2 to 2 ⁄ 3 of cases by switching from AZA to 6MP [63][64][65]. It would be interesting to check, if the GST activity plays a role in the emergence of these side effects.…”
Section: Glutathion-s-transferase (Gst)mentioning
confidence: 99%